Filsafat Behaviorisme Dalam Pendidikan Anak Usia Dini Perspektif Rudolf Steiner - Zahratur Rahma; Maemonah Maemonah (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2021)
This article aims to understand the philosophy of Behaviorism in early childhood education from the perspective of Waldorf (Rudolf Steiner) which is applied to its usefulness in the learning process. Steiner is an educational theory commonly referred to as Waldorf, the word "Waldorf" usually alternates with the term Steiner. Describing schools with a curriculum based on Steiner's teachings is about humans who have ties associated with unraveling the mysteries of the spiritual world. At school Waldorf developed a model to develop creativity in the educational process. Waldorf has a kindergarten that differs from other schools in general. Waldorf educates kindergartens from 3-7 years old. Having a school curriculum that contains games that can hone children's development, such as games that discuss, fairy tales, fables, folklore, these games can increase motor skills and arts. According to the theory of behaviorism the results of learning experiences are the most changes in behavior. The interaction between stimulus and response occurs because of the learning process. The theory of learning behaviorism itself is interpreted to study human behavior, and there are three feelings regarding early childhood education supported by Waldorf teachers: respect, enthusiasm, and protection. a. Respect, enthusiasm and protection, b. Provide a responsive environment, c. Children's relationships with sensory experiences, d. in collaboration with peers, e. Learning by doing, f. Self responsibility and regulation. Keywords: behaviourism; Early childhood education; Waldorf ReferencesAtmojo, W. T. (2013). Penciptaan Batik Medan. Jurnal Pengabdian Kepada Masyarakat, 19(71), 25–34. https://doi.org/10.24114/JPKM.V19I71.4708Bjørnholt, M. (2014). Room for Thinking: The Spatial Dimension of Waldorf Education. RoSE - Research on Steiner Education, 5(1), 115–130. Fahyuni, E. farryatul, & Istikomah. (2016). Psikologi Belajar Mengajar Kunci Sukses Guru dan Peserta didik dalam Interaksi Edukatif. Nizamia Learning Center. Haroen, H. (2014). Kebenaran Pengetahuan, Antara Barat Dan Timur. Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 4(1), 36–47. Maghfhirah, S., & Maemonah. (2019). Pemikiran Behaviorisme Dalam Pendidikan. Jurnal Pendidikan Anak, VI(2), 89–110. Murfi, A. (2017). Posdaya Sebagai Alternatif Pemerataan Pendidikan Anak Usia Dini. Al-Athfal Jurnal Pendidikan Anak, 3(January), 37–50. Naufal, A. (2015). Homeschooling; Paradigma Baru Pendidikan Islam Di Indonesia. Jurnal Tawazun, 8(1), 27–48. Paull, J. (2011). Rudolf Steiner and the Oxford conference: The birth of Waldorf education in Brittain. European Journal of Educational Studies, 3(1), 53–66. Pratama, Y. A. (2019). Relevansi Teori Belajar Behaviorisme Terhadap Pendidikan Agama Islam. Jurnal Pendidikan Agama Islam Al-Thariqah, 4(1), 38–49. https://doi.org/10.25299/al-thariqah.2019.vol4(1).2718Rahmat, S. T. (2018). Filsafat Pendidikan Anak Usia Dini. Jurnal Lonto Leok Pendidikan Anak Usia Dini, 1(1), 1–13. Sari, R. P. (2018). Konsep Pendidikan Waldorf Dalam Karya Rudolf Steiner Dan Relevansinya Dengan Konsep Pendidikan Nasional Republik Indonesia. UPI. Simatupang, D. (2013). Metode Pembelajaran Homeschooling Bagi Anak Usia Dini. In JURNAL PENGABDIAN KEPADA MASYARAKAT (Vol. 19, Nomor 72). https://doi.org/10.24114/JPKM.V19I72.4725Steiner, R. (1995). The Spirit of The Waldorf School. Anthroposophic Press. Suastiningsih, P. E., Wiarta, I. W., & Tirtayani, L. A. (2017). Pengaruh Pembelajaran Menggunakan Pendekatan Saintifik Terhadap Perkembangan Kemampuan Mengenal Warna Pada Anak. Jurnal Pendidikan Anak Usia Dini Undiksha, 4(3). Wattimena, R. A. A. (2016). Pendidikan Filsafat Untuk Anak? Pendasaran, Penerapan Dan Refleksi Kritis Untuk Konteks Indonesia. Jurnal Filsafat, 26(2), 163. https://doi.org/10.22146/jf.12782Yus, A. (2011). Model Pendidikan Anak Usia Dini. Prenadamedia Group. Zalyana, Z. (2016). Perbandingan Konsep Belajar, Strategi Pembelajaran dan Peran Guru (Perspektif Behaviorisme dan Konstruktivisme). Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 13(1), 71–81. https://doi.org/10.25299/al-hikmah:jaip.2016.vol13(1).1512.